2021
DOI: 10.1002/jrs.6291
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of the RBT 04262 Martian meteorite as determined by micro‐Raman and micro‐X‐ray fluorescence spectroscopies

Abstract: Martian meteorites and terrestrial analogs represent the only samples available on Earth for studying mineralogy features of our neighbor planet Mars. This work characterizes the Roberts Massif (RBT) 04262 Martian meteorite by using mainly Raman spectroscopy. By means of this technique, it was confirmed that the meteorite matrix is composed by pyroxene and plagioclase (converted to maskelynite due to the shock pressure). Olivine-coarse grains embedded in the matrix were also observed. These grains were coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…36 Figure 3E shows the Raman bands of marcasite and elemental sulfur, which are 319 (vs) and 381 (s); and 149 (m), 219 (m), 244 (w), and 471 (m), respectively. 6,13 Moreover, in this meteorite, it was observed that the oxidation in an anaerobic environment persisted. Sulfides and elemental sulfur continued to oxidize to anhydrous sulfates, which can hydrate through hydrothermal activity, leading to the formation of hydrated sulfates.…”
Section: Sulfur-rich Mineral Phasesmentioning
confidence: 72%
See 3 more Smart Citations
“…36 Figure 3E shows the Raman bands of marcasite and elemental sulfur, which are 319 (vs) and 381 (s); and 149 (m), 219 (m), 244 (w), and 471 (m), respectively. 6,13 Moreover, in this meteorite, it was observed that the oxidation in an anaerobic environment persisted. Sulfides and elemental sulfur continued to oxidize to anhydrous sulfates, which can hydrate through hydrothermal activity, leading to the formation of hydrated sulfates.…”
Section: Sulfur-rich Mineral Phasesmentioning
confidence: 72%
“…Subsequently, the transfer of S to the crust occurred through volcano degassing, magmatism, and hydrothermal processes, which resulted in a considerable amount of S at the surface. According to Huidobro et al, 6 photochemical activity and the presence of oxidizing agents led to rapid formation of S‐bearing minerals, such as sulfides. If oxidation continued on Mars without the presence of atmospheric oxygen (anaerobic conditions), the primary sulfides may have oxidized to secondary sulfides, 32 elemental sulfur, and sulfates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Huidobro et al [ 9 ] proposed the characterization of the Roberts Massif (RBT) 04262 Martian meteorite. It was confirmed that the meteorite matrix is composed of pyroxene and plagioclase (converted to maskelynite due to the shock pressure).…”
Section: The Importance Of Mars and Space Exploration By Raman Spectr...mentioning
confidence: 99%